The Relationship of Principal Technology Leadership in Curriculum Management and Teacher’s Self-Efficacy - Tisebio Tiop; Roslee Talip (2020)
This study aimed at identify the influence of principal technology leadership in curriculum management towards teachers’ self-efficacy in secondary school district of Kota Kinabalu, Sabah. This is a quantitative research using questionnaire as an instrument and is analyzed using SPSS 25.0. Data was collected through a set of adapted questionnaires administered to 306 teachers. Descriptive and inferential statistics such as percentage, mean, standard deviation, t test, and Pearson correlation were used to analyze the data to answer the research questions. Descriptive analysis principal technology leadership in curriculum management and teachers’ self-efficacy being practised at a high level. Findings of the study showed that there is no significant difference in the min score of principal technology leadership in curriculum management and teachers’ self-efficacy according to gender t(306) = 0.001, k< .05, with mean of principal technology leadership in curriculum management for male (M = 4.349) and female (M = 4.348). While, mean of teachers’ self-efficacy for male (mean =4.342) and female (mean = 4.376). Pearson correlation test indicated a high positive linear relationship for principal technology leadership in curriculum management with teachers’ self-efficacy (r= .460, k< 0.05). The implications and suggestions for further study are also discussed.